ANALYSIS OF INTENTION TO USE THE PUBLIC SERVICE PROGRAM BASED ON THE TANGERANG LIVE APPLICATION AMONG CITIZENS IN TANGERANG CITY USING TECHNOLOGY ACCEPTANCE MODEL - Rizky Meviano, Azriel; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
Public service digitalization is an important element in modern governance to improve efficiency, accessibility, and transparency. However, the implementation of digital applications often faces challenges, as found in the application